2022
DOI: 10.1155/2022/3871994
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence Algorithm-Based Differential Diagnosis of Crohn’s Disease and Ulcerative Colitis by CT Image

Abstract: The aim of this study was to investigate the effect of low-dose CT enterography (CTE) based on modified guided image filtering (GIF) algorithm in the differential diagnosis of ulcerative colitis (UC) and Crohn’s disease (CD). Methods. One hundred and twenty patients with suspected diagnosis of IBD were studied. They were randomly divided into control group (routine CT examination) and observation group (low-dose CTE examination based on improved GIF algorithm), with 60 cases in each group. Comprehensive diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The CT features of inflammatory bowel disease (IBD) typically include wall thickness, sub-mucosal fat, isolated right colon involvement, and mesenteric fibrofatty proliferation. The clinical trial data revealed that the improved GIF algorithm can enhance the application value of low-dose CT images [ 55 ]. Introduced in 1997, CT enterography (CTE) has emerged as the imaging modality of choice for assessing acute IBD [ 56 ].…”
Section: Imaging Of Gastrointestinal Diseasesmentioning
confidence: 99%
“…The CT features of inflammatory bowel disease (IBD) typically include wall thickness, sub-mucosal fat, isolated right colon involvement, and mesenteric fibrofatty proliferation. The clinical trial data revealed that the improved GIF algorithm can enhance the application value of low-dose CT images [ 55 ]. Introduced in 1997, CT enterography (CTE) has emerged as the imaging modality of choice for assessing acute IBD [ 56 ].…”
Section: Imaging Of Gastrointestinal Diseasesmentioning
confidence: 99%
“…Combining the advantages of the wavelet threshold and the bilateral filtering, denoising the image will obtain a better processing effect of image edge detail [20]. As shown in Figure 3, the principle diagram of CT image filtering algorithm [21][22][23][24][25] of wavelet transformation and bilateral filtering is shown.…”
Section: Construction Of Ct Image Processing Model Based Onmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%